Design of Flood Early Detection System using WeMos D1 Mini ESP8266 IoT Technology - Hidayatullah, Muhammad; Andriani, Titi; Azzam, Muhammad R.; Topan, Paris Ali; Esabella, Shinta (Universitas Negeri Malang, 2019)
Flooding is a natural phenomenon caused by water flowing in a volume that exceeds the capacity of the media holding it. The floods affect various human activities. In addition, floods also cause material losses and other related fatalities. To overcome this problem, a flood warning system based on Arduino microcontroller technology and WeMos D1 Mini ESP8266 was designed. The data measured are water level, water velocity, and rainfall. Furthermore, the three data will be combined with Fuzzy logic to make decisions. The output of the system is in the form of a remote command signal that will activate the alarm sound and indicator lights to give a warning to the public about the potential flooding that will occur. The test results show that the measured data has become sufficient information for the microcontroller to generate the corresponding indicator lights and alarm sounds.Â DOI: http://dx.doi.org/10.17977/um024v4i22019p067